Correction: Fractional ABC Dynamics and Nonlinear Transmission Analysis of Dengue–Malaria Co-infection with Reinfection (Earth Systems and Environment, (2026), 10.1007/s41748-026-01258-5) - Lamwong, Jiraporn; Pongsumpun, Puntani (My University, 2026)
The authors wish to correct an error in Figs. 2, 3, 4, 5 and 6 of the above-referenced article (https://doi.org/10.1007/s41748-026-01258-5), with regard to the omission of several subfigures in the online published version. Specifically, subfigures 2g–2q in Fig. 2, subfigures 3g–3q in Fig. 3, subfigures 4g–4h in Fig. 4, subfigures 5g–5h in Fig. 5, and subfigures 6g–6h in Fig. 6 were omitted. The corrected figures are provided below. Time–series dynamics of the dengue–malaria co-infection model under varying fractional orders (ABC derivative) Three-dimensional surface representations of the dengue–malaria co-infection dynamics under varying fractional orders (ABC derivative) Three-dimensional surface plots comparing the effects of different mosquito biting rates on the dengue–malaria co-infection dynamics at the fractional order Three-dimensional surface plots illustrating the impact of varying transmission probabilities from aedes mosquitoes to humans during primary dengue infection at the fractional order Three-dimensional surface plots comparing the effects of different transmission probabilities from dengue-infected humans to aedes mosquitoes during primary infection at the fractional order